Manajemen Supervisi Klinis Kepala Madrasah di MTS Tarbiyah Waladiyah Pulau Banyak - Titania Amelia Putri; Novita Sari; Syarifah Hidayani (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2025)
This study aims to analyse the effect of clinical supervision management by the Head of Madrasah on improving teacher performance at MTsS Tarbiyah Waladiyah Pulau Banyak. This research uses a descriptive qualitative approach with research subjects including the Head of Madrasah and teachers. Data were collected through interviews, observations, and documentation, then analysed systematically using triangulation techniques to ensure data validity. The results showed that: 1) Clinical supervision planning is conducted in a structured manner by involving analyses of teachers' needs and learning situations. The madrasah principal sets specific, realistic and measurable supervision objectives to support the improvement of teachers' abilities and the quality of learning. 2) Clinical supervision involves direct observation, practical guidance and evaluation of learning activities. This process not only focuses on classroom activities, but also includes planning, time management, and use of learning resources. 3) Evaluation of clinical supervision is conducted on an ongoing basis to ensure the relevance of the supervision programme to teachers' needs. This evaluation helps to develop corrective measures and assess the effectiveness of supervision in improving teachers' competencies. This research underlines the importance of systematic clinical supervision in creating positive changes in teaching and learning. Madrasah principals as supervisors have a central role in providing constructive guidance to support teachers' professionalism and improve the overall quality of education.